THE FUZZY ANALYTIC HIERARCHY PROCESS FOR SOFTWARE SELECTION PROBLEMS - Basligil, Huseyin (YILDIZ TECHNICAL UNIV, 2005)
The aim of this study is to provide an analytical tool to select the best software providing the most customer satisfaction. The three type of softwares were examined and the most important criterias were taken into account by the customers while they were selecting their softwares. The fuzzy analytic hierarchy process was used to compare this softwares. The means of the triangular fuzzy numbers were chosen randomly for each comparison were successfully used in the pair wise comparison matrices.
Keywords: AHP; Software Selection; Information Technology; Package Program Selection; Fuzzy Set; Engineering